DESKRIPSI GEJALA DAN PENYEBAB KECEMASAN MATEMATIS MAHASISWA EKONOMI SYARIAH STAI DARUL ULUM KANDANGAN: DESKRIPSI GEJALA DAN PENYEBAB KECEMASAN MATEMATIS MAHASISWA EKONOMI SYARIAH STAI DARUL ULUM KANDANGAN - Abdan Matin Ahmad (Institut Agama Islam Darul Ulum Kandangan, 2021)
The purpose of this study was to reveal the symptoms and causes of mathematics anxiety in students. This study uses a descriptive qualitative method with research subjects including students of the third semester Islamic Economics Study Program STAI Darul Ulum Kandangan. The results showed that subjects with low mathematical anxiety category showed physical symptoms such as nervousness, irritability, or feeling sensitive in carrying out math learning activities. Subjects with the category of moderate mathematical anxiety showed physical and cognitive symptoms such as nervousness, sweaty palms, cold heat, and irritability when faced with math problems. Subjects with the high mathematical anxiety category showed physical symptoms and cognitive symptoms such as nervousness, anxiety, feeling sensitive, heart beating fast, worried, and difficulty concentrating in math learning activities.